2020
DOI: 10.1167/iovs.61.2.6
|View full text |Cite
|
Sign up to set email alerts
|

TNFα-Mediated Priming of Mesenchymal Stem Cells Enhances Their Neuroprotective Effect on Retinal Ganglion Cells

Abstract: Citation: Mead B, Chamling X, Zack DJ, Ahmed Z, Tomarev S. TNFα-mediated priming of mesenchymal stem cells enhances their neuroprotective effect on retinal ganglion cells. Invest Ophthalmol Vis Sci. 2020;61(2):6. https://doi.org/10.1167/iovs.61.2.6 PURPOSE.To determine whether priming of bone marrow mesenchymal stem cells (MSCs) by signals from injured retina, particularly tumor necrosis factor α (TNFα), increase their exosomes' neuroprotective efficacy on retinal ganglion cells (RGCs). METHODS.MSCs were prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…In support of our observation, a prior study reported that MSCs-secreted VEGF mediates the differentiation of endothelial progenitor cells into endothelial cells via paracrine mechanisms [ 47 ]. MSCs-secreted VEGF was also shown to play a part in underlying paracrine and neuroprotective action of MSCs [ 48 ]. NGF is another potential trophic factor that can contribute to enhanced reparative potential of p75 NTR -silenced MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In support of our observation, a prior study reported that MSCs-secreted VEGF mediates the differentiation of endothelial progenitor cells into endothelial cells via paracrine mechanisms [ 47 ]. MSCs-secreted VEGF was also shown to play a part in underlying paracrine and neuroprotective action of MSCs [ 48 ]. NGF is another potential trophic factor that can contribute to enhanced reparative potential of p75 NTR -silenced MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that the presence of WJ-MSCs after the insult is crucial for the improvement of hippocampal cell survival. Importantly, many studies that have assessed the paracrine effects of MSCs have transferred the conditioned medium from MSCs to other cell cultures [ 39 , 40 ]. In the present study, we used a coculture system that allowed the bi-directional interaction between WJ-MSCs and neural cells, without physical contact between the two cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Priming has also been referred to as licensing or preconditioning, which is a concept commonly used in the field of immunology, and it has been adapted to the scope of stem cells [ 144 , 145 ]. One of the commonly used strategies is priming MSCs with pro-inflammatory mediators, including IFN-γ, TNF-α, IL-1α, and IL-1β, and more priming approaches are being proposed to improve the function, survival, and therapeutic efficacy of MSCs [ 146 , 147 ]. The priming approaches could be divided into three categories based on the stimulations: (a) MSCs priming with small molecules, (b) MSCs priming with hypoxia, (c) MSCs priming with biomaterials.…”
Section: Attempts To Improve the Therapeutic Outcomes Of Mscsmentioning
confidence: 99%